Legal protection and enforcement of human rights against the increasing impact of child labour - Alvin Aditya Fajar Setiawan (Requisitoire Law Enforcement, 2023)
The state has the responsibility to defend and uphold the human rights of its citizens. One of the many vulnerable groups that are the focus of human rights violations are children. Because they are a vulnerable group that does not have special rights, children need protection. Countries around the world committed to revisit the issue of child protection by ratifying the Convention on the Rights of the Child in 1989. Employment of minors is one of the most persistent violations of children's rights. Working children lose their rights to develop, play, and obtain education. Therefore, the role of the government is to provide facilities and accessibility for children, especially to ensure optimal and directed growth and development. The protection and provision of basic rights for every citizen must be recognised, upheld and guaranteed by the State.